Evenings near the village of Dikanka : stories published by bee-keeper Rudi Panko - Gogol, Nikolai Vassilievitch, (Classics of russian literature)
The fair at Sorochintsi. -- Saint John's eve. -- A may night ; or The drowned maiden.--The lost letter. -- Christmas eve. -- A terrible revenge. -- Ivan Fyodorovich Shponka and his aunt. -- A place bewitched.